2016
DOI: 10.1155/2016/3975101
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Implications in the Affective Disorders: Main Biomarkers, Animal Models Relevance, Genetic Perspectives, and Antioxidant Approaches

Abstract: The correlation between the affective disorders and the almost ubiquitous pathological oxidative stress can be described in a multifactorial way, as an important mechanism of central nervous system impairment. Whether the obvious changes which occur in oxidative balance of the affective disorders are a part of the constitutive mechanism or a collateral effect yet remains as an interesting question. However it is now clear that oxidative stress is a component of these disorders, being characterized by different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 291 publications
(292 reference statements)
0
62
0
1
Order By: Relevance
“…A complex interaction between genetic predisposition [22], lifestyle choices [34,35], psychological and other stressors [36] trigger immune abnormalities towards a proinflammatory state and induce OS. These changes lead to progressive cellular and structural damage [11,37], resulting in symptoms related to the underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A complex interaction between genetic predisposition [22], lifestyle choices [34,35], psychological and other stressors [36] trigger immune abnormalities towards a proinflammatory state and induce OS. These changes lead to progressive cellular and structural damage [11,37], resulting in symptoms related to the underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is bidirectionally associated to OS, also present in schizophrenia and mood disorders [22]. OS induces cell damage due to an imbalance in the release of toxic-free radicals (reactive oxygen species, ROS) from redox reactions over protective antioxidants.…”
Section: Os In Mood and Psychotic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that elements termed biometals are altered in the cortex of patients with mood disorders and suicide completers. These biometals are increasingly recognised as being central to maintaining oxidative balance in the CNS (Pokusa and Trancikova, 2017), a mechanism considered particularly important in the pathophysiology of mood disorders (Balmus et al, 2016;Berk et al, 2011) and open to therapeutic intervention (Ng et al, 2008) through biometal homeostatic restoration (Robert et al, 2015). By contrast, the pathways by which metals are involved in suicide remain to be elucidated and our findings indicate that further exploration into the utility of blood 1,1,113 1,1,113 1,1,113 1,1,113 1,1…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments we have analyzed the effects of cholinergic and catecholaminergic agonists (pilocarpine, clonidine and pergolide), applied in various combinations, on working and reference memory, assessed through the eight radial arms maze test in rats, as well as on basic oxidative stress markers, considering the increased awareness regarding the implications of the oxidative stress status in various neuropsychiatric disorders, including dementia [5,6,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%